PENGALAMAN NUH SEBAGAI MODEL PEMBELAJARAN DALAM TEOLOGI PENGANIAYAAN: IMPLIKASI TERHADAP PEMUDA DALAM PENDIDIKAN AGAMA KRISTEN - Haelitik, Apriana (Inculco Journal of Christian Education, 2024)
Abstract: Persecution has emerged throughout human history. It often arises from differences in power, faith, ethnicity and social background, causing global suffering. This study aims to understand: What is Noah's experience as a learning model in the theology of persecution? What are the implications for youth today? What is the contribution to Christian religious education? The methodology used is a graphic subjective examination strategy using written studies. The results obtained are that Noah's experience provides a learning model for the importance of integrity, obedience to God, and resilience in facing challenges, living in love and justice, with God providing opportunities for repentance. The implication for today's youth is to build moral integrity and obedience to God's will as the foundation of strong character. Youth are expected to defend the truth, practice obedience to God's principles, and become agents of moral and spiritual change amidst the challenges of life. Contributions to Christian Religious Education help youth understand the root of problems, develop empathy, and take responsibility, forming the basis of moral education with a focus on justice, love, and solidarity, to encourage their role as agents of social change for justice and peace.